Integration of Health Information Systems to Improve Emergency Management in Primary Care at Sembiring General Hospital Deli Tua in 2023 - Ridwanto Situmeang (Medistra Medical Journal (MMJ), 2025)
Catastrophic emergencies, such as natural disasters, mass accidents, and pandemics, demand preparedness and resilience. Primary care plays a crucial role as the frontline in handling medical emergencies. Speed, accuracy, and strong coordination are key to saving patients' lives. However, challenges often arise, including delays in data recording, difficulty accessing medical records, and suboptimal communication between units. Health information system integration presents an innovation to address these challenges through digital, real-time, and interconnected data management across service units. This study aims to analyze the role of health information system integration in improving emergency management at Sembiring Deli Tua General Hospital in 2023. The research method used a descriptive qualitative design using interviews, observations, and document review techniques. Research informants included Emergency Unit healthcare workers, medical records officers, and hospital information system managers. The results showed that the implementation of a health information system can accelerate the triage process, improve the accuracy of patient records, and strengthen coordination between healthcare workers in critical situations. Consequently, the response to emergency patients becomes more efficient and targeted. Obstacles still encountered include limited technological infrastructure, human resource skills, and suboptimal policy support. In conclusion, health information system integration has proven to contribute significantly to improving emergency management in primary care. Going forward, strengthening digital infrastructure, improving healthcare worker competency, and managerial commitment will be key factors.